Fabrication of graphene oxide-Ti3AlC2 synergistically reinforced copper matrix composites with enhanced tribological performance. Issue 15 (15th October 2019) - Lian, Weiqi; Mai, Yongjin; Wang, Jie; Zhang, Liuyan; Liu, Cansen; Jie, Xiaohua
Abstract: Ceramic particles reinforced copper (Cu) matrix composites with good electrical conductivities, superior mechanical and tribological properties show great prospect in electrical contacts, thermal management and sliding bearing materials. A novel Cu matrix composite with low coefficient of friction (COF) and high wear resistance is rationally designed and prepared by hot-press sintering the core-shell structured Cu/graphene oxide (GO)/Cu composite powders and Cu decorated Ti3 AlC2 particles to achieve homogenous dispersion of GO in the Cu matrix and good interfacial bonding of Cu matrix and GO and Ti3 AlC2. Its tribological performance and corresponding anti-wear alongside with friction reduction mechanisms at room temperature are systematically investigated. The GO-Ti3 AlC2 synergistically enhanced Cu matrix composite exhibits lower COF and wear rate than those composites reinforced with GO or Ti3 AlC2 alone, for GO and Ti3 AlC2 synergistically bear the load and form continuous, compact and lubricating tribo-layer on the worn surface.